BETWEEN TRADITIONALIST AND MODERNIST: THE ISLAMIC REFORMATION OF HAJI ABDUL LATIF SYAKUR IN MINANGKABAU IN THE 20TH CENTURY - Yosi Nofa; Mohd Roslan Mohd Nor (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2023)
This paper discusses the thoughts of Haji Abdul Latif Syakur in the context of Islamic reform in Minangkabau in the twentieth century. He is a figure who cannot be associated with traditional Islam or modern Islam. Haji Abdul Latif Syakur was able to become a traditionalist and modernist Muslim at the same time. In Islamic thought, traditionalists and modernists are not contradictory to each other. This study answers the Islamic views of Haji Abdul Latif Syakur and his position on the dichotomy of traditionalist and modernist Islamic thought. This study shows that Haji Abdul Latif Syakur was involved in Islamic reform efforts in Minangkabau in the early twentieth century. His thoughts of reform went beyond modernist ideas and his Islamic view was also not the same as traditionalist. He has an independent Islamic perspective. This study concludes that apart from traditionalists and modernists, other groups have participated in shaping Islamic buildings in Minangkabau. This third group is accepted by two other groups, traditionalists and modernists. This research is qualitative research with historical and sociological approaches. The focus of the research is the work of Haji Abdul Latif Syakur which is related to the theme of the idea of ​​Islamic reform.